Inventory: The pesticides application and its risk assessment in the irrigated perimeter of Tadla-Morocco - Hafiane Fatima Zahra; Bouzaidi Hind El; Nouayti Nordine; Tahri Latifa; Jarmouni Mohamed El; Didi Salahdine; Fekhaoui Mohammed (Limnological Review, 2021)
The industrialization of the agricultural sector increases the use of pesticides, which are composed of chemical substances, such as herbicides, fungicides, insecticides, acaricides, nematicides, and rodenticides, that are adapted to the control of undesirable plants and animals. All these phytosanitary products have varying degrees of toxicity, which risks human life. This study aimed to make an inventory of the pesticides used in the irrigated perimeter of Beni Moussa and Beni Aamir in the Beni Mellal-Khenifra region. The data collection through questionnaires took place between January and February 2016 and covered all the study areas. The questionnaires are focused on the mode of packaging management, sale and purchase of pesticides. The results demonstrated the existence of different pesticides and active substances used for crop protection in the region. Among 63 molecules, 14 active substances were detected, where the active substances are not approved by the world health organization, which considers it as carcinogenic substances. During phytosanitary treatments by farmers, these active substances come into direct contact with the soil, presenting a permanent risk to the environmental compartments, including groundwaters.